POLCAGE 1.0 - A possibilistic life-cycle assessment model for evaluating alternative transportation fuels - Tan, Raymond Girard R. (Animo Repository, 2004)
A composite software model for the comparative life-cycle assessment (LCA) of 10 different fuel options for the Philippine automotive transport sector was developed. It is based on the GREET fuel-cycle inventory model developed by the Argonne National Laboratory for the United States Department of Energy. GREET 1.5a is linked to an impact assessment submodel using the Danish environmental design of industrial products (EDIP) method. This combined inventory-impact assessment model is enhanced further with possibilistic uncertainty propagation (PUP) and possibilistic compromise programming (PCP) features that allow the 10 alternatives to be ranked in the presence of multiple criteria and uncertain data. Sensitivity and scenario analysis can also be performed within the composite model. Some current and anticipated Philippine conditions, including electricity generation mix, are incorporated in the prototype's built-in database. The software model, designated as POLCAGE 1.0 (possibilistic LCA using GREET and EDIP), is coded in Microsoft Excel and Visual Basic. The model's capabilities and features are demonstrated using a case study based on its default scenario. © 2003 Elsevier Ltd. All rights reserved.